2005
DOI: 10.1186/bf03351823
|View full text |Cite
|
Sign up to set email alerts
|

The terdiurnal tide in the mesosphere and lower thermosphere over Wuhan (30°N, 114°E)

Abstract: Winds measured by an all-sky meteor radar have been used to investigate the terdiurnal tide in the mesosphere and lower thermosphere (MLT) region over Wuhan (30.6 • N, 114.4• E). We present a climatology of the terdiurnal tide at low-mid latitude site during the period of April 2002 to December 2004. The terdiurnal peak is distinct in the long-term power spectrum of the wind. The monthly and seasonal mean maximum amplitudes have values of 7 m/s and 5 m/s, respectively. The short-term amplitudes can occasiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…In recent years, new ground-based instruments have been built in China to monitor the mesosphere and lower thermosphere, including the digital ionosonde [6], the meteor radar [7][8][9][10][11], and the atmosphere gravity wave imager [12] in China. Some researchers have analyzed international observational data obtained by FPIs [13].…”
mentioning
confidence: 99%
“…In recent years, new ground-based instruments have been built in China to monitor the mesosphere and lower thermosphere, including the digital ionosonde [6], the meteor radar [7][8][9][10][11], and the atmosphere gravity wave imager [12] in China. Some researchers have analyzed international observational data obtained by FPIs [13].…”
mentioning
confidence: 99%
“…For example, regular annual variation of the wave phase was observed in the meridional wind at Wuhan (30 • N) and Wakkanai (45.4 • N) (Namboothiri et al, 2004;Zhao et al, 2005), and in the zonal wind at London, Canada (43 • N) (Thayaparan, 1997). The vertical wavelength reported by the previous studies was found to vary widely, over a range from 12 to more than 1000 km.…”
Section: Introductionmentioning
confidence: 82%
“…The features and seasonal variabilities of the diurnal tide and semidiurnal tide in the mesosphere and lower thermosphere (MLT) have been quite well investigated through observations and model simulations (Manson and Meek, 1986;Teitelbaum et al, 1989;Thayaparan, 1997;Pendleton et al, 2000;Smith, 2000;Smith and Ortland, 2001;Akmaev, 2001;Younger et al, 2002;Batista et al, 2004;Namboothiri et Correspondence to: G. Jiang (gyjiang@spaceweather.ac.cn) al., 2004;Taori et al, 2005;Zhao et al, 2005;Beldon et al, 2006;Tokumoto et al, 2007). Nevertheless, the 8-h tide, as a distinct wave signature in the MLT region, is not well understood, especially compared to the diurnal tide and semidiurnal tide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst several of those studies addressed the tidal effects and characteristics in the middle (e.g. Forbes, 1984) and upper atmosphere (Forbes and Garrett, 1979;Forbes, 1990;Thayaparan, 1997;Zhao et al, 2005), we concentrate, for reasons of comparability, on troposphere-based observations and theories (e.g. Haurwitz, 1956;Kertz, 1956;Dai and Wang, 1999).…”
mentioning
confidence: 99%